Surgical Management of Charcot Spinal Arthropathy Using a Quadruple-Rod Construct: A Proof of Concept. (16th November 2020) - Pierre, Clifford A; von Glinski, Alexander; Elia, Christopher; Ansari, Darius; Ishak, Basem; Blecher, Ronen; Frieler, Sven; Qutteineh, Bilal; Hopkins, Sarah; Oskouian, Rod J; Chapman, Jens
Abstract: INTRODUCTION: Charcot spinal arthropathy (CSA) is a rare complex spinal condition often found in patients many years after a spinal cord injury. Although previously presented in case reports and series, there is no consensus regarding best treatment methods. General consensus for treatment at our institution involves utilization of a quadruple-rod construct, while infected CSA was treated in a two staged approach using temporary rod fixation and Poly (Methyl Methacrylate (PMMA) Spacer. This study aims to investigate clinical and radiological outcomes of surgical treatment for patients with Charcot spinal arthropathy in order to optimize care. METHODS: Our prospectively collected spine surgery database was retrospectively reviewed for all patients diagnosed and surgically treated with CSA at a single institution. Charts reviewed to assess complications and the need for reoperation. RESULTS: A total of 17 patients with CSA were identified and underwent surgical intervention with a mean follow up time of 16.79 months (16.79 (SD 14.71, range 0.27 - 47.7 months). All patients except for 2 had a quadruple-rod construct; exceptions were secondary to patient refusal or medical reasons. A total of 5 (29.4%) patients required reoperation; 3 for wound revision, 1 for misplaced screw, and only 1 (5.9%) for instrumentation failure/pseudarthrosis. CONCLUSION: CSA is a complex condition in patients many years after spinal trauma. We recommend aggressive management with use of bone morphoenetic protein (BMP), and the use of a quadruple-rod construct to provide maximum fixation and prevent instrumentation failure or pseudoarthrosis. In the setting of infected CSA requiring extensive anterior column debridement we recommend a staged procedure with segmental fixation with temporary rod placement and antibiotic impregnanted Polymethylmethacrylate (PMMA) placed in the anterior column dead space followed by PMMA removal and cage placement after antibiotic therapy completion. Utilizing this treatment regimen we have obtained favorable results treating this patient population.